SISTEM PENDUKUNG KEPUTUSAN UNIVERSITAS FAKULTAS TERBAIK UNIVERSITAS LANCANG KUNING MENGGUNAKAN METODE SMART DAN MOORA - Roki Hardianto; Fana Wiza; Wirdah Choiriah (LPPM Universitas Abdurrab, 2021)
Decision Support System (SPK) is a system that can help the leader / owner in the decision making process by using a calculation method based on assessment criteria. DSS is not a decision making tool but only a comparison tool in decision making. The Best Faculty Decision at Lancang Kuning University is a process of evaluating faculties from several aspects of criteria that can help leaders / quality assurance bodies in assessments with the aim of creating competition among faculties of assessment. The research will be carried out using comparison of assessment results using Smart and Moora methods. The results of the decisions of each method will be seen effectiveness in the assessment process to become a decision. In each method using the same or different criteria, it depends on the weight value of each criterion that is assessed. This result can be a reference for Lancang Kuning University in evaluating the assessment of the Best Faculty based on aspects of assessment.